Novel Cell-Based Assay for Alpha-3 Nicotinic Receptor Antibodies Detects Antibodies Exclusively in Autoimmune Autonomic Ganglionopathy. Issue 3 (29th May 2022) - Karagiorgou, Katerina; Dandoulaki, Maria; Mantegazza, Renato; Andreetta, Francesca; Furlan, Raffaello; Lindstrom, Jon; Zisimopoulou, Paraskevi; Chroni, Elisabeth; Kokotis, Panagiotis; Anagnostou, Evangelos; Tzanetakos, Dimitrios; Breza, Marianthi; et al.
Abstract : Background and Objectives: Autoantibodies against α3-subunit–containing nicotinic acetylcholine receptors (α3-nAChRs), usually measured by radioimmunoprecipitation assay (RIPA), are detected in patients with autoimmune autonomic ganglionopathy (AAG). However, low α3-nAChR antibody levels are frequently detected in other neurologic diseases with questionable significance. Our objective was to develop a method for the selective detection of the potentially pathogenic α3-nAChR antibodies, seemingly present only in patients with AAG. Methods: The study involved sera from 55 patients from Greece, suspected for autonomic failure, and 13 patients from Italy diagnosed with autonomic failure, positive for α3-nAChR antibodies by RIPA. In addition, sera from 52 patients with Ca 2+ channel or Hu antibodies and from 2, 628 controls with various neuroimmune diseases were included. A sensitive live cell-based assay (CBA) with α3-nAChR–transfected cells was developed to detect antibodies against the cell-exposed α3-nAChR domain. Results: Twenty-five patients were found α3-nAChR antibody positive by RIPA. Fifteen of 25 patients were also CBA positive. Of interest, all 15 CBA-positive patients had AAG, whereas all 10 CBA-negative patients had other neurologic diseases. RIPA antibody levels of the CBA-negative sera were low, although our CBA could detect dilutions of AAG sera corresponding to equally low RIPA antibody levels. No serum bound to control-transfected cells, and none of the 2, 628 controls was α3-CBA positive. Discussion: This study showed that in contrast to the established RIPA for α3- nAChR antibodies, which at low levels is of moderate disease specificity, our CBA seems AAG specific, while at least equally sensitive with the RIPA. This study provides Class II evidence that α3-nAChR CBA is a specific assay for AAG. Classification of Evidence: This study provides Class II evidence that an α3-nAChR cell-based assay is a more specific assay for AAG than the standard RIPA.